(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to examine the types and meaning of conceptual metaphor of love that appear in Olivia Rodrgio’s spng lyrics on the SOUR album. Conceptual metaphor describes abstract concepts using more concrete terms. This study uses Lakoff and Johnson theory, which classifies conceptual metaphor into three types: orientational metaphor structural metaphor, and ontological metaphor. This research uses qualitative method with a descriptive approach. The data was obtained through documentation method, by analyzing the lyrics of each song in Sour album used Conceptual metaphor theory (CMT) by Lakoff and Johnson to find the metaphors. The result show that there 59 conceptual metaphors of love, consisting of 4 orientational metaphor, 23 structural metaphor, and 32 ontological metaphors. This conceptual metaphor is used to represent various experiences of love, such as emotional journey, heartbreak, and struggles with self-identity. The use of conceptual metaphor in these song lyrics aims to emphasize the expression of feelings and convey messages more creatively and deeply.